Evaluation of Antibacterial Activity and Toxicity Effects of Newbouldia Stem Bark Extract - Umaru, Kerenhappuch Isaac; Umaru, Isaac John; Tansaba, Akafa Andes; Nanmar, Chakfa; Ugoeze, Egeonu Stephen (Darul Yasin Al Sys, 2024)
Newbouldia leavis is a boundary tree. it is a medium size angiosperm which belongs to the Bignoniaceae family. It is a fast-growing evergreen shrub or small tree. This study was carried out to investigate antibacterial activity of the methanol extract of Newbouldia stem bark. The antibacterial activity of the methanol extracts was determined by the agar well diffusion method. Three standard bacterial strains: Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae were used for the antibacterial assay. Result of screening plant extracts for antibacterial activity showed that most of the organisms were sensitive to the extract. The antibacterial test utilizing well diffusion assay showed that Gram-positive bacteria were more susceptible to the plant extract compared to Gram-negative bacteria. This study supports the use of Newboulda leavis in traditional medicine as well as highlights the need to further explore the potentials of the plant extract as antibacterial agent.